ROLE OF LODHRA AND NYAGRODHA IN SHVETA PRADARA-COMPARING TWO DIFFERENT MODALITIES OF TREATMENT - Sharma Sabarad, Priya; G.C, Jayasudha; M, Ramesh (International Journal of Ayurveda and Pharma Research, 2015)
In the present world, a woman has to play an active role in home as well as social and professional arena. While trying to strike a balance, she tends to neglect her health, which leads to various problems. Shveta pradara (excessive white discharge p/v) is one such problem faced by women of all age groups. This problem is a cause of major concern these days due to its recurrent nature as well as immense discomfort that it causes. Not only this, it causes other associated problems like lower back ache, dyspareunia etc. If left untreated, it causes complications such as pelvic inflammatory disease and even infertility. In the present study, 40 diagnosed patients of Shveta pradara (excess white discharge per vaginum) between age group 18 to 45 years were selected and divided into two groups: Group A and Group B, where each group had 20 patients. Group A Yoni prakshalana (vaginal wash) with Kashaya (decoction) prepared from bark (Twak) of Lodhra as well as Nyagrodha was done for 7 consecutive days along with Pathya ahara vihara (congenial diet and lifestyle advice). Group B- were given Lodhra Twak (bark) Churna (fine powder) of 4g with Nyagrodha twak kashaya of 16ml. orallywith luke warm water as Anupana (adjuvant) for 10 consecutive days along with Pathya ahara vihara. On comparing the two groups, it was found that the efficacy of treatment in Group A was better than efficacy of treatment in Group B which means that Yoni prakshalana had a better effect on Shveta pradara.